Greek women now have an equal voice - Irene Kamberidou (SPOTLIGHT, a Fortnightly Publication for Political Studies, publication of the Institute of Political Studies (I.P.S), no. 1, May 18, 1984: 2., 1984)
Kamberidou, Irene (1984). Greek women now have an equal voice. SPOTLIGHT, a Fortnightly Publication for Political Studies, publication of the Institute of Political Studies (I.P.S),  no. 1, May 18, 1984: 2.